Islamic Financial Infrastructure towards the Establishment of Sharia Central Banks - Agus Pandoman (PT FORMOSA CENDEKIA GLOBAL, 2022)
History notes that America has gotten two giant economic crises both the Great Depression of 1930s and the Financial Crisis of 2008’s. On August 15, 1971 the United States Dollar went down drastically. Without Congressional approval, President Nixon ended the coinage between the United States Dollar and the gold. Consequently the dollar becomes Monopoly Money. After that, the biggest economic boom in history has begun. In 2009, when the economy ran aground, Central Bankers in the world created trillion dollars, yen, pesos, euros and pounds by following a monopoly for bankers.1 The concept has changed to the present time. The distribution of money has become a concept of debt in various forms, including the use of money as a capital instrument. The main contributors to capital in Islamic trade traffic (muamalah) are economic real, not loans (non-loans), actors who direct money used for business capital are concentrated in the form of financing, but after the end of the Gold standard (fiat money), how far the meaning of financing can fulfill justice based on Islamic economics. The concept of the Bank is any camouflage with the money industry, and it is not clear enough, exactly the difference between the Bank and Islamic nuances, because all financial industries are under one container, namely the interest-base central bank. In short, Islamic banking with a financing system, while conventional banking with a loan system. Two different central banks are greatly needed.